Study of diseases prevalence among children in areas of spacerocket activity - G. Ya. Evlashevsky (Бюллетень сибирской медицины, 2002)
An objective of this investigation is to study disease prevalence in children residing at territories of falling of separable parts from second stages of space crafts rocket-carriers. The areas of falling and the adjacent areas are the territories of increased ecological risk. The reason is that they are used as dumps for wastes from space-rocket activity: metal fragments of worn-out second stages of rocket-carriers and toxic guarantee remnants of liquid rocket fuel components. In the scope of the study a profound medical examination of children (0—14 years) has been conducted. The main and control group included correspondingly 750 and 312 children. Obtained intensive, extensive and standardized rates of pathological affection have been analyzed (table 1—3). Prevalence rates of pathologies in children residing at territories, adjacent to areas of falling of parts of rocketcarriers, increase significantly the control rates. This fact provides steady scientific claims for discussion of direct association between the observed pathology and prolonged space-rocket activity in the region.